Clinical Significance of the Neutrophil–to–Lymphocyte Ratio in Endocrine Therapy for Stage IV Breast Cancer - IIMORI, NOZOMI (In Vivo, 2018)
Background: Studies have found that patients with cancer exhibit abnormal leukocyte fractions, such as elevated neutrophil count and diminished lymphocyte count, and that the neutrophil-to-lymphocyte ratio (NLR) provides a surrogate marker for prognosis and response to treatment of patients after radical surgery for several different types of cancer. However, few reports have addressed the association between the NLR and response to endocrine therapy. In this study, we carried out a clinical investigation to confirm whether or not the NLR predicted the response to endocrine therapy of stage IV breast cancer. Patients and Methods: The study subjects were 34 patients who underwent endocrine therapy as initial drug therapy for stage IV breast cancer. The correlation between NLR and prognosis, including the efficacy of endocrine therapy, was evaluated retrospectively. Results: Among the 34 patients, the NLR was high in 10 (29.4%) and low in 24 (70.6%). In analysis of outcomes, the group with low NLR had a significant prolongation of progression-free survival (p=0.003), time to treatment failure (p=0.031), and overall survival (p=0.013) compared to the group with high NLR. Univariate analysis of progression-free survival found that responding to treatment [hazard ratio (HR)=4.310, p=0.004] and low NLR (HR=3.940, p=0.016) were factors associated with a favorable prognosis. Multivariate analysis also showed that responding to treatment (HR=4.329, p=0.006) and low NLR (HR=3.930, p=0.008) were independent factors associated with a favorable prognosis. Conclusion: Our results suggested that the NLR may represent a predictive marker for response to endocrine therapy in stage IV breast cancer.